Spin Dynamics in Ferromagnet/10-nm-Thick N-Type GaAs Quantum Well Junctions - 纪晓晨;申超;吴元军;鲁军;郑厚植 (Chinese physics letters, 2017)
Spin dynamics in several different types of ferromagnetic metal （FM）/10-nm-thick n-type GaAs quantum well （QW） junctions is studied by means of time-resolved Kerr rotation measurements. Compared with the MnGa/insitu doped lO-nm-thick n-type GaAs QW junction, the spin lifetime of the MnGa/modulation-doped 10-nm-thick n-type GaAs QW junction is shorter by a factor of 6, consistent with the D＇yakonov Perel＇ spin relaxation mechanism. Meanwhile, compared with the spin lifetime of the MnAs/in-situ doped 10-nm-thick n-type GaAs QW junction, the MnGa/in-situ doped 10-nm-thick n-type GaAs QW junction is of a spin lifetime longer by a factor of 4.2. The later observation is well explained by the Rashba effect in the presence of structure inversion asymmetry, which acts directly on photo-excited electron spins. We demonstrate that MnGa-like FM/in-situ doped 10-nm-thick n-type GaAs QW junctions, which possess relatively low interfaciai potential barriers, are able to provide long spin lifetimes.